A Review of Emerging Technologies in Robotic Arm for Sorting Applications - Joseph, Ojotu Ijiwo; Ayodeji, Sesan Peter; Adeyeri, Michael Kanisuru (Journal of Advanced Industrial Technology and Application, 2026)
In recent times, the growing complexity and scale of manufacturing operations have necessitated the need for a robust material handling system. One of the most important revolutions in this area is the application of a robotic arm to sorting operations. This review provides an overview of the advances in robotic sorting systems, outlining the interactions among component parts. More than 50 peer-reviewed journal articles from 2015 to 2025 were considered for the analysis. Statistical findings show that 4-dof robotic arms dominate the literature with 32%, while Arduino microcontrollers and color as a sorting criterion remain the most widely adopted with 69% and 51% respectively, due to their affordability and ease of use. The survey classifies the present robotic technologies according to a three-level taxonomy: perception, decision, and execution, while stressing the interdependency of this framework. Furthermore, the review recommends the application of reconfigurability, artificial intelligence (AI), and multimodal sensing technologies to existing robotic sorting systems as a means of increasing intelligence and the flexibility of future robotic sorting systems.